História e Sociologia das Práticas de Leitura: a trajetória de seis leitores oriundos do meio rural - Manke, Lisiane Sias (2012)
The theme of this thesis is the study of the trajectories of readers who come from the rural area; its main objective is to understand the development of reading practices through the analysis of individual structures, by investigating: a) the social circumstances of the past which contributed in the process of incorporating reading inclination.; b) the means and the modes of reading and the reading appropriation of six rural actors. The theoretical tenets which guided the analysis are related to the history of reading studies, regarding the proposals of Roger Chartier, and the sociology of reading and the culture concepts discussed by Bernard Lahire. The investigation was performed with individuals living in the southern region of Rio Grande do Sul State, known in their locale as assiduous readers. They are six readers, four men and two women born and raised in the rural area, over 70 years old, with poor schooling and daily reading in a non-professional way. The methodological approach is related to the proposal of sociology on an individual scale, in which the individual must be deeply investigated, to apprehend the inner plurality of unique individuals. Thus, from four to six interviews were taken profoundly with each one of the readers investigated. The analysis of these readers trajectories made possible the outline of an image of reading practices in the social world, evincing the reader as unique individual in the social field, pervaded by sociability relations which constitute him. In doing so, this research results demonstrated that different instances of socialization contribute to the process of incorporating reading inclination, and that the readers experience different relations with reading during their life trajectory, by being subordinated to internal forces (inclinations) and to external forces (contexts) which interfere in action. Considering the modes of reading, the analysis evinced silent and extensive reading practices, i.e., lonely and silent readings of a significant number of texts, except the reading practice of a Bible reader . Referring to the modes of appropriation of texts, it was possible to notice some ethic-pratical inclinations, in which one may assume participation, identification with the read text, related to a sociohistorical identity of the readers.